A Fourier series model and parametric study for single person three-way continuous walking load - Li, Ping (Transactions on Computer Science and Intelligent Systems Research, 2024)
The characteristics and mathematical model of the walking load is the basis for studying   human-induced vibration in large-span flexible structures. In this paper, 2842 sets of effective walking load datum were collected by three-way force plate test. The correlation analysis shows that the correlations between the vertical component, the horizontal component and the longitudinal component of the walking load are weak, the Fourier series models of the three directional components of the walking load are established. The model parameters of the dynamic loading factor, the phase angle and the walking frequency function with respect to walking frequency are analyzed statistically, and the function of dynamic load factor and phase angle with respect to walking frequency are obtained respectively. Compared with the existing walking load model, it shows that there are some differences from the former models.